Progress Test in nursing: perspectives for undergraduate education - Bruna Moreno Dias; Lúcia Marta Giunta da Silva; Marina de Góes Salvetti; Carmen Silvia Gabriel (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to reflect on the perspectives of adopting the Progress Test in undergraduate nursing education. Methods: this is a reflective study, based on authors' critical thinking and supported by national and international literature on the Progress Test application in undergraduate health courses. Results: the Progress Test is as a valuable teaching-learning strategy, with potential applications and benefits for students, professors, and academic management. Final considerations: systematic nursing education assessment indicates valuable information for different stakeholders. Understanding its potential benefits, the Progress Test is presented as a strategy that can be replicated in undergraduate nursing education, either individually, by institutions, or collaboratively, by the establishment of partnerships or consortiums of institutions.